Mengukur Disparitas Regional dan Pola Pertumbuhan Ekonomi di Provinsi Papua Barat: Aplikasi Tipologi Klassen, Indeks Williamson, dan Indeks Theil - Hans Sammy Marthin Salakory; Febby Sonya Matulessy (Journal of Innovative and Creativity, 2025)
The difference in the content of the natural resources, concentrated economic activities in several cities and regencies, and the inadequate utilization of the sea and land for economic activities affect the difference in development and economic growth in cities and regencies throughout West Papua. This study aims to calculate and analyze the economic patterns and structures as well as regional disparities in West Papua. To answer the research issues, the analysis technique used is quantitative descriptive with Klassen typology analysis tools, Williamson index, and Thail Entropy Index. The results of the research and data analysis show that there are no cities and regency in West Papua which are high growth and high income, only the category of high income but low growth, namely Sorong Regency, Bintuni Bay. Regency and Cities that are high growth but low income are Sorong city, Fakfak, South of Sorong, Manokwari, Raja Ampat. Furthermore, low growth and low income are Maybrat, Kaimana, Arfak Mountains, South of Manokwari, Tambrauw. There has been a very high inequality in the research period, as evidenced by the Williamson index average of 1.53, and the Entropy Thail Index of 0.25. On the other side, this inequality has decreased over time, but Kuznets' inverted-U hypothesis does not apply to the economy of West Papua. The trigger for inequality is the difference in the content of natural oil and gas resources, centralized activities in several cities and regencies and much of the productive land is being neglected for economic activity.